PERAN PEMERINTAH DESA DALAM MENGELOLA BADAN USAHA MILIK DESA (BUMDES) - Valentine Queen Chintary; Asih Widi Lestari (JISIP : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
Abstract : The role of rural government on institutional management is the foremost unit of society development. Especially Rural-Own Enterprises , as the government program that has to be empowered in order to realize the good socio-economic empowerment of society by prioritizing the society participation and initiatives. The goal of this research is to knowing the rural government role on managing Rural-Own Enterprises and to knowing the Rural-Own Enterprises programs of Bumiaji village, Batu. This research is kind of a qualitative method. The research sampling that used is a purposive sampling with the informants like the Headman of Bumiaji village, the village Secretary, the Village Chief of Banaran, Head of Government Affairs, Rural-Own Enterprises Administrators, Rural-Own Enterprises administrator, and two residents of Bumiaji village. The data collection technique that used by the researcher were an interview, observation, and documentation. While the data analysis method that used is descriptive. The results of this research prove that the rural government's role of Bumiaji village in managing Rural-Own Enterprises is, as the formation and development's institution of Rural-Own Enterprises, as the training mediator and motivator of the organization's member formation and also as the controller of Rural-Own Enterprises. The Bumiaji Village's Rural-Own Enterprises programs are the establishment of the Village Prosperity Agency , The Association of the Drinking Water Users , and the Arjuna Gelora Management Agency. Keywords: Rural, Government Role, managing and Rural-Own Enterprises Abstrak : Peran Pemerintah Desa dalam pengelolaan kelembagaan merupakan unit terdepan pembangunan kepada masyarakat. Terutama Badan Usaha Milik Desa (BUMDes) merupakan program pemerintah yang harus diberdayakan dalam rangka pemberdayaan sosial ekonomi masyarakat. yang baik dengan mengedepankan partisipasi dan prakarsa masyarakat. Tujuan penelitian ini adalah untuk mengetahui Peran Pemerintah Desa dalam mengelola BUMDes dan mengetahui program BUMDes di Desa Bumiaji Kota Batu. Penelitian yang dilakukan merupakan penelitian kualitatif. Sampel penelitian mengunakan purposive sampling dengan informan yaitu Kepala Desa Bumiaji, Sekretaris Desa, Kepala Dusun Banaran, Kepala Urusan Pemerintahan, Pengurus BUMDES, Pengelola BUMDES dan sebanyak dua orang masyarakat desa Bumiaji. Teknik pengumpulan data yang dilakukan oleh peneliti adalah wawancara, observasi dan dokumentasi. Metode analisa data yang digunakan yaitu metode deskriptif. Hasil penelitian membuktikan bahwa peran pemerintah Desa Bumiaji dalam mengelola BUMDes yakni sebagai pembentukan dan pengembangan BUMDes, sebagai mediator pelatihan dan motivator terhadap terbentuknya pengurus dan organisasi BUMDes serta sebagai pengawasan. Sedangkan program BUMDES di Desa Bumiaji Kota Batu seperti terbentuknya Badan Kesejahteraan Desa (BKD), Himpunan Penduduk Pemakai Air Minum (HIPPAM) dan Badan Pengelola Gelora Arjuna (BAPEGAR). Kata kunci: Peran, Pemerintah Desa, mengelola dan BUMDES